Monocyte-Derived Dendritic Cells Dictate the Memory Differentiation of CD8+ T Cells During Acute Infection - Shin, Kwang-Soo; Jeon, Insu; Kim, Byung-Seok; Kim, Il-Kyu; Park, Young-Jun; Koh, Choong-Hyun; Song, Boyeong; Lee, Jeong-Mi; Lim, Jiyoung; Bae, Eun-Ah; Seo, Hyungseok; Ban, Young Ho; et al. (Frontiers in Immunology, 2019)
Monocyte-derived dendritic cells (moDCs) have been shown to robustly expand during infection; however, their roles in anti-infectious immunity remain unclear. Here, we found that moDCs were dramatically increased in the secondary lymphoid organs during acute LCMV infection in an interferon-γ (IFN-γ)-dependent manner. We also found that priming by moDCs enhanced the differentiation of memory CD8+ T cells compared to differentiation primed by conventional dendritic cells (cDCs) through upregulation of Eomesodermin (Eomes) and T cell factor-1 (TCF-1) expression in CD8+ T cells. Consequently, impaired memory formation of CD8+ T cells in mice that had reduced numbers of moDCs led to defective clearance of pathogens upon rechallenge. Mechanistically, attenuated interleukin-2 (IL-2) signaling in CD8+ T cells primed by moDCs was responsible for the enhanced memory programming of CD8+ T cells. Therefore, our findings unveil a specialization of the antigen-presenting cell subsets in the fate determination of CD8+ T cells during infection and pave the way for the development of a novel therapeutic intervention on infection.